Centro de desarrollo comunitario - LGBTI - barrio Gabriela Mistral - escala sectorial - Loayza Loor, Ana Michelle (2019)
The urban proposal made in the ARO-960 workshop proposes to make the sector of the Mariscal a centrality of the city of Quito due to its uses, functions, public spaces, mobility systems, equipment and patrimonial buildings. This proposal is made in order to triple the number of inhabitants of the sector by the year 2040. The proposal is based on improving mobility, preserving heritage and supplying the sector with facilities and public spaces that improve the quality of life of users in the sector. Depending on the analyses, a number of strategically distributed equipment was proposed throughout the sector, which may have an educational, cultural, social, health or housing character in order to supply the sector. The urban-architectural intervention to work in this thesis proposes a cultural-social equipment, which responds to the needs of users, mainly the LGBTI group. The LGBTI-focused community center will base its form and function on contextual, program and user studies. The main goal of the community center is to meet the most important need of the LGBTI community which is to integrate into society and be accepted despite their sexual diﬀ erences.